RESPON GURU DAN SISWA TERHADAP IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMKN 1 PULOAMPEL - Marwan (Rabbani: Jurnal Pendidikan Agama Islam, 2023)
SMKN 1 Puloampel is an educational unit that implements an independent curriculum with the independent category changing, meaning that the school provides flexibility to use the learning tools that have been provided. Although only class X uses an independent curriculum, all subjects of class X, including Islamic Religious Education lessons, must refer to an independent curriculum. The research method used in this writing is to use a descriptive analysis method with a qualitative approach and use a direct observation method through the results of interviews. With the warm issue that arises, namely the change in curriculum from the 2013 curriculum to an independent curriculum, SMKN 1 Puloampel tries to implement an independent curriculum by regulating in accordance with the rules in it, including various parties in schools also support the implementation of an independent curriculum. Teachers and students responded well to the implementation of the independent curriculum at SMKN 1 Puloampel